IMPLEMENTASI PENGEMBANGAN SUMBER DAYA MANUSIA TENAGA PENDIDIK PADA AKADEMI KEPERAWATAN RUMKIT TKT. III TELING MANADO SULAWESI UTARA - Sururama, Rahmawati (Institut Pemerintahan Dalam Negeri, 2018)
Abstract Human Resource Management Higher education emphasizes the intricate parts of the figure of a lecturer as an ordinary human and intellectual community group (educated) that can be elaborated in scientific and cultural studies (Arwildayanto, 2013). Based on the above problems the researcher took the title “Implementation of Human Resource Development Teachers at the Academy of Nursing Rumkit Tkt. III Teling Manado” so that future every lecturer can meet academic qualification standards in order to improve the quality of college. Through the preliminary observations that have been carried out in the Academy of Nursing Tkt. III Teling Manado that the existing problems are still lack of permanent lecturers, educational qualifications and lecturer status that has not been in accordance with the competency standards of the existing lecturers as many as nine people but who qualify only three people, others have not studied S-2. This research is designed using qualitative descriptive research method.Data collection techniques and procedures in this study besides observation, interviews and documentation, this study also used triangulation data collection techniques. The focus of this research is the Implementation of Human Resource Development lecturer At Nursing Academy Rumkit Tkt. III Teling Manado “. The findings obtained: 1. Development brings changes in behavior toward specialization, differentiation and professionalism of teaching staff in the field of teaching, personal, social and professional. 2.Upaya maintain consistency of professional ability of educator done both by educator and institute of college iu herself, so that result optimally to improvement of professionalism of educator can sustainable. Keywords: implementation, human resource development, educators